Identification and evaluation of BAG (B-cell lymphoma-2 associated athanogene) family gene expression in pigeonpea (Cajanus cajan) under terminal heat stress - Alekhya, Chakravaram; Tejaswi, Avuthu; Harika, Gadeela; Bomma, Naresh; Gangashetty, Prakash I.; Tyagi, Wricha; Yogendra, Kalenahalli (Frontiers in Genetics, 2024)
IntroductionHeat stress poses a significant environmental challenge, impacting plant growth, diminishing crop production, and reducing overall productivity. Plants employ various mechanisms to confront heat stress, and their ability to survive hinges on their capacity to perceive and activate appropriate physiological and biochemical responses. One such mechanism involves regulating multiple genes and coordinating their expression through different signaling pathways. The BAG (B-cell lymphoma-2 associated athanogene) gene family plays a multifunctional role by interacting with heat shock proteins, serving as co-chaperones, or regulating chaperones during the response to heat stress and development. While numerous studies have explored BAG proteins in model plants, there still remains a knowledge gap concerning crop plants.MethodsOur study successfully identified nine BAG genes in pigeonpea through genome-wide scanning. A comprehensive in silico analysis was conducted to ascertain their chromosomal location, sub-cellular localization, and the types of regulatory elements present in the putative promoter region. Additionally, an expression analysis was performed on contrasting genotypes exhibiting varying heat stress responses.ResultsThe results revealed eight CcBAG genes with higher expression levels in the tolerant genotype, whereas BAG6 (Cc_02358) exhibited lower expression. Upstream sequence analysis identified BAG members potentially involved in multiple stresses.DiscussionThe functional characterization of these BAG genes is essential to unravel their roles in signaling pathways, facilitating the identification of candidate genes for precise breeding interventions to produce heat-resilient pigeonpea.